2021
DOI: 10.3390/su132112133
|View full text |Cite
|
Sign up to set email alerts
|

The Ethically Conscious Flower Consumer: Understanding Fair Trade Cut Flower Purchase Behavior in Germany

Abstract: Fair trade flowers are an important niche product relevant to ethically conscious consumers. The study proposes a model that investigates key factors affecting the behavior of these cut flower consumers in Germany. The study serves to complement the existing studies dedicated to preferences for flower attributes and products, as well as consumers’ willingness to pay. It builds on an online survey with a representative sample of 772 German cut-flower consumers. Partial least squares structural equation modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…, 2019). This barrier can be overcome through the expansion of the range of FT coffee (Cailleba and Casteran, 2010), the utilization of price as an indicator of its quality (Rombach et al. , 2021), or the better dissemination of its ethical implications (Robichaud and Yu, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…, 2019). This barrier can be overcome through the expansion of the range of FT coffee (Cailleba and Casteran, 2010), the utilization of price as an indicator of its quality (Rombach et al. , 2021), or the better dissemination of its ethical implications (Robichaud and Yu, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, one of the most significant obstacles to achieving these goals is the high price of FT coffee (De Pelsmacker and Janssens, 2007;Lappeman et al, 2019). This barrier can be overcome through the expansion of the range of FT coffee (Cailleba and Casteran, 2010), the utilization of price as an indicator of its quality (Rombach et al, 2021), or the better dissemination of its ethical implications (Robichaud and Yu, 2022). Thus, on the one hand, FT coffee managers should offer higher ranges of products, from premium FT coffee brands to competitively priced FT coffee (Cailleba and Casteran, 2010).…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of marketing, consumer consciousness guides consumer behavior, and only by understanding the cognitive process of consumers can their behavior be explained [33]. Rombach and others found that the moral awareness of German cut-flower consumers' concern about labor and the environment affected their attention to fair trade as an attribute of cut flowers, which further affected their purchasing behavior [34]. Graham-Rowe [35] and Ju [36] explored the psychological obstacles of British and South Korean consumers to the adoption of electric vehicles, respectively.…”
Section: Consciousnessmentioning
confidence: 99%